2019
DOI: 10.2147/ccide.s192847
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical applications of intraoral camera to increase patient compliance - current perspectives</p>

Abstract: Technological advancements in the field of dentistry have reformed the concept of photography as a powerful medium of expression and communication. It also offers a spectrum of perception, interpretation, and execution. One of the widespread clinical applications of computerization in dentistry today is the intraoral camera (IOC). It helps in the revelation of the hidden and overlooked defects in teeth and other parts of the cavity. Dental world constitutes of microstructures that have to be recorded in a deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Intraoral photographs can be beneficial for conducting dental public health surveys, especially in suburban areas. It could be utilised as an effective medium of communication between the patient and dentist [ 8 ] and in advancing tele-dentistry [ 34 ]. Intraoral photographs may be captured by a smartphone, professional single-reflex lens camera with flash, or intraoral camera for clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoral photographs can be beneficial for conducting dental public health surveys, especially in suburban areas. It could be utilised as an effective medium of communication between the patient and dentist [ 8 ] and in advancing tele-dentistry [ 34 ]. Intraoral photographs may be captured by a smartphone, professional single-reflex lens camera with flash, or intraoral camera for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of dentistry, novel techniques beneficial for patients and clinicians are being developed. One such device is an intraoral camera (IOC), which is inexpensive, easy to operate with digital storage, and capable of capturing high-quality images [ 8 , 9 ]. It has also been shown that caries can be identified simply and reliably using the IOC [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…21 Low-cost intra-oral cameras may facilitate the identification of previously hidden and often overlooked defects in teeth and other parts of the oral cavity. 22 Previous reports have documented their use in recording carious lesion appearance in the patient record, and they may also be of significant benefit in monitoring early lesions over time following their detection. 23,24 This benefit extends not only to dentists but also to patients, for whom it may be a useful educational and motivational tool.…”
Section: Use Of Diagnostic-imaging Multiformat Cameras For Identification Of Oral Lesionsmentioning
confidence: 99%
“…The bene its of Intraoral cameras are early detection of oral health problems, improved patient-doctor relation, improves the accuracy of the advised treatment, for future case documentation, enhances doctor's credibility and better for insurance (Karthiga et al, 2018). Pictures can be given to a patient's document for future reference (Pentapati and Siddiq, 2019). The advantages of Intraoral cameras are early identi ication of oral medical issues, improved patient-doctors connection, improves the quality of the treatment, for future case documentation, upgrades doctors believability and better protection claims (Neuman, 1996).…”
Section: Intraoral Cameramentioning
confidence: 99%